9*(x-5)+4*(6-x)=3+3*(x+20)-2x5*(y-1)-3*(y-2)=7-y+3 решите...
24 февраля 2013 - Администратор
Рейтинг: 0
Голосов: 0
530 просмотров
Комментарии (0)
Нет комментариев. Ваш будет первым!
9*(x-5)+4*(6-x)=3+3*(x+20)-2x
5*(y-1)-3*(y-2)=7-y+3
решите пожалуйста. В школу завтра 8. 00
9х-45+24-4х=3+3х+60-2х
9х-4х-3х+2х=45-24+3+60
4х=84
х=84:4
х= 21
5у-5-3у+6=7-у+3
5у-3у+у=5-6+7+3
3у=9
у=9:3
у=3
9(х-5)+4(6-х)=3+3*(х+20)-2х
9х-45+24-4х=3+3х+60-2х
9х-4х-3х+2х=3+60+45-24
4х=84
х=21
5(у-1)-3(у-2)=7-у+3
5у-5-3у+6=10-у
5у-3у+у=10-6+5
3у=9
у=3
Источник: https://znanija.com/task/234472
Нет комментариев. Ваш будет первым!